Multimorbidity in the working-age population of Serbia: Results from the 2019 National Health Survey - Radić Ivana; Harhaji Sanja; Dragnić Nataša; Mijatović-Jovanović Vesna; Čanković Sonja; Čanković Dušan (Vojnosanitetski Pregled)
Background/Aim. Population aging and the increase in the prevalence of chronic diseases led to a rise in the number of people who live with more than one disease. The aim of the study was to determine the prevalence and predictors of multimorbidity in the working-age population (WAP) of Serbia. Methods. The study is part of “The 2019 Serbian National Health Survey”, a c ross-sectional study conducted on a representative stratified two-stage sample. For this paper, a representative data sample for 9,473 persons of the WAP (aged 15–64 years) was used. Multimorbidity was defined as the co-occurrence of two or more of 13 chronic conditions. Data on chronic conditions were self-reported, and data on body mass and body height were measured. Multivariable logistic regression was used to assess predictors of multimorbidity. Results. Multimorbidity prevalence among WAP was 12.0%, and it was significantly higher among women (13.3%) than in men (10.6%). The predictors of multimorbidity were: female gender, increasing age, lower level of education, lower income, unemployment, retirement, widowhood, and divorce. Being overweight and obese were associated with higher odds of multimorbidity in both men and women. Conclusion. Multimorbidity is an important public health problem amongst WAP in Serbia due to its high prevalence, especially among vulnerable groups, and its inequality in frequency among different socioeconomic groups.